Feline Calicivirus Prevalence among Cats in Turkey's Kayseri Province - Abayli, H.; Can-Sahna, K.; Ozbek, R.; Bekdik, Karaca, I (Israel Veterinary Medical Assoc, 2020)
Feline calicivirus (FCV) is a highly contagious pathogen, which is common in the cat population. The present study investigated the prevalence of FCV and potential risk factors for infection in the cat population in Turkey's Kayseri province. The study group comprised clinically healthy cats (n = 67) and cats displaying signs of FCV infection (n = 26). The animals varied in term of breed, age, gender, vaccination status, and housing status (shelter vs. outdoor). Swab samples were obtained and tested for FCV using a commercial enzyme-linked immunosorbent assay (ELISA) kit and semi-nested reverse-transcription polymerase chain reaction (RT-PCR) assay with a new primer design. From a total of 93, ten samples were positive for FCV according to the ELISA, and 18 samples were positive according to the semi-nested RT-PCR test. The positivity rate was found to be higher in semi-nested RT-PCR than ELISA. The overall prevalence of FCV infection was 19.35% (18/93). A risk factor analysis revealed that breed, age, gender, housing status and vaccination status were not risk factors for FCV. There was a statistically significant difference only in clinically healthy cats and symptomatic cats (p < 0.001). The study revealed the presence of FCV in both asymptomatic cats and vaccinated cats. The semi-nested RT-PCR with newly designed primers may be beneficial for researchers.
Keywords: Feline Calicivirus; Semi-Nested RT-PCR; ELISA; Turkey